Conductive Metal-Organic Frameworks for Amperometric Sensing of Paracetamol - Wang, Jing; Liu, Sen; Luo, Jiahuan; Hou, Shaogang; Song, Haixiang; Niu, Yongsheng; Zhang, Chuanxiang (Frontiers in Chemistry, 2020)
An electrochemical sensor for paracetamol is executed by using conductive MOF (NiCu-CAT) which is synthesized by 2, 3, 6, 7, 10, 11-hexahydroxytriphenylene (HHTP) ligand. The utility of this 2D NiCu-CAT is measured by the detection of paracetamol, p-stacking within the MOF layers is essential to achieve high electrical conductivity, redox activity, and catalytic activity. In particular, NiCu-CAT demonstrated detection Limit of determination near 5 μM for paracetamol through a wide concentration range (5 μM - 190 μM). The NiCu-CAT/GCE exhibits excellent reproducibility, stability and interference for paracetamol.